Resistance and recovery studies on ultraviolet-irradiated spores of Bacillus pumilus. - Abshire, R L (1980)
A spore suspension model and a procedure for recovering ultraviolet (UV)-irradiated spores of Bacillus pumilus were investigated. A most-probable-number tube dilution method using double-strength Trypticase soy broth was found to be superior to the agar plate method for recovering optimal numbers of spores irradiated with sublethal doses of UV energy. Aqueous suspensions of B. pumilus survived UV doses up to 108,000 ergs/mm2 as determined by a most-probable-number recovery and estimation procedure. Resistance and stability data were consistent and reproducible, indicating the dependability of this method for recovering UV-damaged spores. The procedures used to collect information concerning resistance characteristics for two strains of B. pumilus are discussed.